Le Littéraire dans le quotidien - Luks, Joanna Gay (Open textbook library., 2015)
Le Littéraire dans le quotidien is an open textbook for use in French courses. The Literary in the Everyday represents a new pedagogical approach to reading and writing at the lower levels and is applicable to all languages. Teachers of foreign languages besides French can read about the approach in the Teacher's Guide. Go to Google Drive for individual chapters. Additionally, the Foreign Languages & The Literary in the Everyday (FLLITE) Project, a joint initiative of COERLL and CERCLL, two national foreign language resource centers, offers open resources for professional development in the publication of CC licensed FLLITE lessons in any language.